1983
DOI: 10.1136/vr.112.6.116
|View full text |Cite
|
Sign up to set email alerts
|

Experimental cryptosporidiosis in calves: clinical manifestations and pathological findings

Abstract: Twenty-two calves between one and 20 days old were infected orally or by contact with cryptosporidia. Calves were maintained as either specific pathogen free, colostrum fed or sucking and were inoculated with either a bacteria free or a contaminated cryptosporidium preparation. Enteritis was characterised by depression, anorexia and diarrhoea and cryptosporidium oocysts were excreted during the clinical course of the illness. In the initial stages of the disease, cryptosporidium infestation was found throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 0 publications
4
63
0
2
Order By: Relevance
“…Furthermore, Iseki (10) Cryptosporidium may be a common cause of diarrhea among infants and children, particularly in developing countries (11)(12)(13)(14). Experimental studies have shown that young animals are more susceptible than older ones to Cryptosporidium infection (15,16). Our study also showed that the infection was more common among younger cats, although it was detected also in older ones.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, Iseki (10) Cryptosporidium may be a common cause of diarrhea among infants and children, particularly in developing countries (11)(12)(13)(14). Experimental studies have shown that young animals are more susceptible than older ones to Cryptosporidium infection (15,16). Our study also showed that the infection was more common among younger cats, although it was detected also in older ones.…”
Section: Discussionsupporting
confidence: 60%
“…In another study, 100% of mice were infected with the same infective dose (10 5 oocysts per mouse), remaining infected during the first 15 days pi (Novak and Sterling 1991). In view of the foregoing, it was decided to use a very high infective dose of 5×10 5 oocysts per mouse, so as to enable the study of the infection during the 6th to the 16th days pi, a period similar to that for which cryptosporidiosis is present in ruminants Tzipori et al 1983;Snodgrass et al 1984;OrtegaMora and Wright 1994;Fayer et al 1998). In this respect, most of the studies so far carried out using a neonatal mice model have checked the efficacy of therapeutic or prophylactic measures (drugs or antibodies) in controlling cryptosporidiosis on only 1 day, frequently the 7th day pi Blagburn et al 1998).…”
Section: Od (450 Nm)mentioning
confidence: 99%
“…as primary entero-pathogens was uncertain until 1980, when Tzipori et al (1980) attributed an outbreak of neonatal diarrhea to cryptosporidial infection alone. In the following years methods to free the infective oocysts from other contaminating pathogens become available, which permitted the experimental demonstration that Cryptosporidium was capable of causing clinical diarrhoea in calves (Tzipori et al, 1983;Heine et al, 1984). In cattle, two species of the genus Cryptosporidium were distinguished, C. parvum is infecting the distal small intestine and C. muris infecting the abomasum.…”
Section: Introductionmentioning
confidence: 99%